La fuerza electromotriz de polarización y el potencial químico del hidrógeno y del oxígeno atómicos - Tedeschi, Virgilio (1938)
The author has measured the electromotive force of polarization with various original procedures finding values superior to those calculated with the thermodynamic equation of Lord Kelvin or to those anticipated in the equation of Lord Kelvin and Helmholtz. The fact is attributed to the greater chemical potential of the atomic hydrogen and oxygen which are the immediate products of electrolytic process.